Ibudilast reduces alcohol drinking in multiple animal models of alcohol dependence. (11th November 2013) - Bell, Richard L.; Lopez, Marcelo F.; Cui, Changhai; Egli, Mark; Johnson, Kirk W.; Franklin, Kelle M.; Becker, Howard C.
Abstract Neuroinflammatory signaling pathways in the central nervous system are of current interest as potential pharmacotherapy targets for alcohol dependence. In this study, we examined the ability of ibudilast, a non‐selective phosphodiesterase inhibitor, to reduce alcohol drinking and relapse in alcohol‐preferring P rats, high‐alcohol drinking HAD1 rats, and in mice made dependent on alcohol through cycles of alcohol vapor exposure. When administered twice daily, ibudilast reduced alcohol drinking in rats by approximately 50% and reduced drinking by alcohol‐dependent mice at doses which had no effect in non‐dependent mice. These findings support the viability of ibudilast as a possible treatment for alcohol dependence.